SPONTANEOUS ACHILLES TENDON RUPTURE - A CASE OF OCHRONOSIS - Shetty, Sanath Kumar; R., Raj Sankar N.; P., Nirmal Babu; Mathias, Lawrence J.; Bhat, Shubha P.; Rai, Ravindranath (Journal of Health and Allied Sciences NU, 2013)
Alkaptonuria is a rare autosomal recessive disorder characterised by the absence of homogentisic acid oxidase and the subsequent accumulation of homogentisic acid, a metabolic product of the aromatic aminoacids phenylalanine and tyrosine; which is deposited in articular cartilages, intervertebral discs, sclera, tympanic membrane, tendons and ligaments leading to their degeneration. Here we describe a case of spontaneous rupture of Achilles tendon1,2,3 due to Ochronosis.
Keywords: Alkaptonuria; Ochronosis; Achilles tendon